2008
DOI: 10.5650/jos.57.139
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Components of the Straw of Oryza sativa L.

Abstract: The components of the volatile oils from the straws of Oryza sativa L. (Onshinomai, Asamurasaki, Hinohikari) were analyzed by capillary GC/GC-MS. The quantification of volatile compounds in the oils was made by the internal standard method, using palmitic acid as reference substance. Palmitic acid was the most abundant component in these samples, followed by hexahydrofarnesyl acetone and phytol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Identification of the individual components was based on the following: i comparison of their GC-MS retention indices RI on apolar and polar columns with those of authentic compounds or literature data 7 ; the RIs are determined relative to the retention times of a series of n-alkanes C8-C29 ; ii computer matching with commercial mass spectral libraries 8 , and comparison of spectra with literature data 9 . The quantitative composition of the oil was analyzed by GC-FID assuming the total of the oil to be 100 .…”
Section: Identi Cation Of Componentsmentioning
confidence: 99%
“…Identification of the individual components was based on the following: i comparison of their GC-MS retention indices RI on apolar and polar columns with those of authentic compounds or literature data 7 ; the RIs are determined relative to the retention times of a series of n-alkanes C8-C29 ; ii computer matching with commercial mass spectral libraries 8 , and comparison of spectra with literature data 9 . The quantitative composition of the oil was analyzed by GC-FID assuming the total of the oil to be 100 .…”
Section: Identi Cation Of Componentsmentioning
confidence: 99%
“…Many researchers have studied volatile compound in raw and cooked rice, 2-acetyl-1-pyrroline (2-AP; popcorn aroma) was reported as an important contributor to be the aroma characteristic of rice [5][6][7][8][9] . Straw of rice also reported on volatile components, palmitic acid was the most abundant component, followed by hexahydrofarnesyl acetone and phytol 10) . Reports on red and black rice are very few, studies only the suppressive effect of the SOS-inducing activity 11) , tyrosinase inhibitor of black rice bran 12) in our previous papers, and antioxidant activity of purple black rice 13) .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the FD-factors, it was found that β-caryophyllene oxide 60; FD-factor 128, spicy was the most intense (Tronto, Canada); Other, reference mass spectrum and retention index were measured outside the author' s laboratory (the identification is therefore considered to be tentative). e Our previous studies: 21 from miyazawa et al 14) ; 45, 47 from miyazawa et al 15) ; 56 from miyazawa et al 16) ; 63, 64, 73, 77 and 85 from miyazawa et al 17,18) ; 66 from miyazawa et al 19)…”
Section: Gc-o Aeda and Rfamentioning
confidence: 99%